MEMBACA AL-JABIRI: MENGGALI INSPIRASI DARI POST-TRADISIONALISME ISLAM - Siti A'isyah (JURNAL PUSAKA, 2015)
Al-Jabiri’s thought, one of prominent thinkers of Islamic reform, considered as one with original ideas. His two main ideas, namely turats and hadatsah and epistemological critique of Islam (Arabic) is considered unique, despite the criticism leveled by some thinkers. The idea of turats and hadatsah emphasis on more comprehensive reading on turats accompanied by a more productive reading. His criticism on the epistemology of Islam (Arabic), which departed from the mapping of Arabic reason, is very popular; Bayani-Burhani-Irfani. These Al-Jabiri’s ideas, especially about turats and hadatsah, are inspiring this article. It can be used as a telescope to look at Pesantren tradition that became the basis of Al-Qolam tradition as well as its area of concern contained in its vision "to be the best Research Islamic Unibersity Based on Pesantren in East Java in 2030". Turats reading and methods of reading on turats initiated by Al-Jabiri could be adopted by Al-Qolam in defining and reading the Pesantren tradition.Keywords: turats and hadatsah, pesantren, the vision of Al-Qolam